Encapsulation of curcumin in polymeric nanoparticles for antimicrobial Photodynamic Therapy - Trigo Gutierrez, Jeffersson Krishan [UNESP]; Zanatta, Gabriela Cristina [UNESP]; Ortega, Ana Laura Mira [UNESP]; Balastegui, Maria Isabella Cuba [UNESP]; Sanitá, Paula Volpato [UNESP]; Pavarina, Ana Cláudia [UNESP]; Barbugli, Paula Aboud [UNESP]; De Oliveira Mima, Ewerton Garcia [UNESP] (Public Library of Science (PLoS), 2017)
Curcumin (CUR) has been used as photosensitizer in antimicrobial Photodynamic Therapy (aPDT). However its poor water solubility, instability, and scarce bioavalibility hinder its in vivo application. The aim of this study was to synthesize curcumin in polymeric nanoparticles (NP) and to evaluate their antimicrobial photodynamic effect and cytoxicity. CUR in anionic and cationic NP was synthesized using polylactic acid and dextran sulfate by the nanoprecipitation method. For cationic NP, cetyltrimethylammonium bromide was added. CUR-NP were characterized by physicochemical properties, photodegradation, encapsulation efficiency and release of curcumin from nanoparticles. CUR-NP was compared with free CUR in 10% dimethyl sulfoxide (DMSO) as a photosensitizer for aPDT against planktonic and biofilms (mono-, dual- and triple-species) cultures of Streptococcus mutans, Candida albicans and Methicillin-Resistant Staphylococcus aureus. The cytotoxicity effect of formulations was evaluated on keratinocytes. Data were analysed by parametric (ANOVA) and non-parametric (Kruskal-Wallis) tests (α = 0.05). CUR-NP showed alteration in the physicochemical properties along time, photodegradation similar to free curcumin, encapsulation efficiency up to 67%, and 96% of release after 48h. After aPDT planktonic cultures showed reductions from 0.78 log10 to complete eradication, while biofilms showed no antimicrobial effect or reductions up to 4.44 log10. Anionic CUR-NP showed reduced photoinactivation of biofilms. Cationic CUR-NP showed microbicidal effect even in absence of light. Anionic formulations showed no cytotoxic effect compared with free CUR and cationic CUR-NP and NP. The synthesized formulations improved the water solubility of CUR, showed higher antimicrobial photodynamic effect for planktonic cultures than for biofilms, and the encapsulation of CUR in anionic NP reduced the cytotoxicity of 10% DMSO used for free CUR.